2004
DOI: 10.1161/01.cir.0000129305.25115.80
|View full text |Cite
|
Sign up to set email alerts
|

Increased Atrial and Brain Natriuretic Peptides in Adults With Cyanotic Congenital Heart Disease

Abstract: Background-Brain natriuretic peptide (BNP) levels are used in the evaluation of patients with heart disease, yet there is little understanding of the effect of hypoxia on natriuretic peptide secretion. Furthermore, recent data suggest that oxytocin may mediate stretch-induced atrial natriuretic peptide (ANP) secretion. Methods and Results-Ten patients with cyanotic congenital heart defects and 10 control subjects were studied. N-terminal proatrial natriuretic peptide and N-terminal probrain natriuretic peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(44 citation statements)
references
References 23 publications
2
40
2
Order By: Relevance
“…In the current study, patients with other reasons for a high [NT-proBNP] were excluded, and the timing and the conditions surrounding NTproBNP sampling were standardised. A recent study has reported a close relationship between Sv,O 2 and [NT-proBNP] in patients with cyanotic congenital heart disease and PH [49]; however, Sv,O 2 did not predict [NT-proBNP] in the present study, and patients with CHD were specifically excluded. The present authors wish to emphasise that their conclusions can only be applied to selected PH patients assessed in the described manner.…”
Section: Study Limitationscontrasting
confidence: 87%
“…In the current study, patients with other reasons for a high [NT-proBNP] were excluded, and the timing and the conditions surrounding NTproBNP sampling were standardised. A recent study has reported a close relationship between Sv,O 2 and [NT-proBNP] in patients with cyanotic congenital heart disease and PH [49]; however, Sv,O 2 did not predict [NT-proBNP] in the present study, and patients with CHD were specifically excluded. The present authors wish to emphasise that their conclusions can only be applied to selected PH patients assessed in the described manner.…”
Section: Study Limitationscontrasting
confidence: 87%
“…Although these values increased in sepsis (Varpula et al 2007), the mechanism for the increase is not clear. This is believed to be related to various causes such as IL-1β , TNF-α (Harada et al 1999;Court et al 2002), IL-6 (Tanaka et al 2004), lipopolysaccharide of Gram-negative bacteria (Tomaru et al 2002), neurosecretory hormones (Ma et al 2005;Clerico et al 2006), hypoxia (Hopkins et al 2004), renal dysfunction, coagulation disorders and the suppression of cardiac muscle (Varpula et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is thought that over-secretion of the hormone is caused by hypoxia, leading to pulmonary vasoconstriction, pulmonary hypertension, and right-heart overload [39,40]. Accordingly, exposure of healthy individuals to hypoxia gradually raises circulating ANP levels [41][42][43][44]. Some authors claim that only pulmonary disease including both chronic exposure to hypoxia and pulmonary hypertension, may cause an increase in ANP levels [44].…”
Section: Discussionmentioning
confidence: 99%